2011
DOI: 10.1002/pen.21991
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing conditions on the development of morphological features of banded or nonbanded spherulites of poly(3‐hydroxybutyrate) (PHB) and polylactic acid (PLLA) blends

Abstract: Two semicrystalline poly(3-hydroxybutyrate) (PHB) and polylactic acid (PLLA) blends with and without poly (vinyl acetate) (PVAc) were prepared by dissolving different ratios in hot chloroform at 50 8C to obtain promising alternative biodegradable materials for eliminating plastic waste. The miscibility, crystallization, melting behavior and vibration modes of the prepared samples were characterized by differential scanning calorimetry (DSC), polarized optical microscopy (POM), Fourier transform infrared spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 46 publications
(82 reference statements)
0
31
0
Order By: Relevance
“…For example, the addition of a suitable amount of PVAc to both PMMA and PPC makes the blends fully miscible [20] . The addition of PVAc to the two immiscible polymers namely PLLA and PPC [7,9] served to improve the physical properties of the blend [8,21] . However, it has been demonstrated that increasing the PVAc in its blends with the PDLA [22] reduces the enzymatic degradation rate of PLLA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the addition of a suitable amount of PVAc to both PMMA and PPC makes the blends fully miscible [20] . The addition of PVAc to the two immiscible polymers namely PLLA and PPC [7,9] served to improve the physical properties of the blend [8,21] . However, it has been demonstrated that increasing the PVAc in its blends with the PDLA [22] reduces the enzymatic degradation rate of PLLA.…”
Section: Introductionmentioning
confidence: 99%
“…has investigated that the addition of a small amount of PHB to PLLA can used as accelerating agent for improving the crystallization process in PLLA [6] . PLLA is immiscible with PHB [7] , two phase separations was found in 50%/50% wt (PLLA/PHB blends) [7] but a small amount of PHB (<25%) is miscible with PLLA [6] . PVAc was used as compatibilizer to improve the miscibility between PLLA and PPC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, it is interesting to note that the addition of PVAc into the PPC/PLA blend gives rise to not only a peak shifting of the C=O stretching band (from 1742 to 1739 cm -1 ) but also an obvious peak broadening, suggesting that PVAc is likely to improve the interaction between PPC and PLA molecules. The potential molecular mechanisms for the enhanced interaction may be the CH 3 … O=C interaction, as in the case for PHB/PLA/PVAc blends proposed by El-Hadi [28]. To give a direct evidence on the validity of this assumption, the FTIR spectra of neat PPC, PLA, and PPC/PVAc and PLA/PVAc blends were measured.…”
Section: Molecular Mechanisms For the Compatibilizationmentioning
confidence: 99%